SCENARIO PLANNING AS A TOOL FOR DEVELOPING LONG-TERM STRATEGIC DIRECTION: A CASE STUDY OF PT RAJATRANS INDONESIA - Ramadhani Meifariza; Pri Hermawan (Jurnal Media Ekonomi (JURMEK), 2026)
Purpose: This study examines how scenario planning can support long-term strategic decision-making in a newly established premium tourism transportation company operating under conditions of uncertainty. Research Methodology: A qualitative single-case study was conducted at PT Rajatrans Indonesia. Data were collected through four semi-structured interviews representing internal, industry, customer-partner, and government perspectives and triangulated with secondary data from public and industry sources. The Garvin and Levesque framework operationalized through Chermack (2022) guided the analysis. Results: Two critical uncertainties were identified: the trajectory of domestic premium tourism demand and the intensity of competition in the premium segment. These uncertainties generated four plausible scenarios: Open Road, Race to the Top, Quiet Lane, and Survival Premium. The findings indicate that Rajatrans possesses competitive strengths through its luxury fleet, bundled service model, and referral network, but faces organizational vulnerabilities related to founder dependence, digital capability, and financial system development. Contributions: The study provides evidence of scenario planning applicability within a newly established micro-enterprise and demonstrates how divergent stakeholder perspectives may function as useful indicators of strategic uncertainty. The resulting framework combines foundational capability development with scenario-specific strategic responses to strengthen long-term organizational resilience.